PENDIDIKAN BERBASIS ISLAMIC EDUCATION: KAJIAN PEMIKIRAN HADRATUS SYAIKH K.H HASYIM ASY'ARI DALAM KITAB ADABUL ALIM WA MUTA'ALIM - Wahdah , Akhmad Bahril (Al Tadib : Jurnal Ilmu Pendidikan, 2025)
This study examines the thoughts of KH. Hasyim Ash'ari about Islamic education-based education in the book Adabul Alim wa Muta'alim. as the key to the success of education. Departing from the challenge of educational and moral degradation, this study aims to examine the concept of value-based education contained in the book Adabul Alim wa Muta'alim. The method used is literature research by studying the works of KH. Hasyim Asy'ari. The results of the study show that it emphasizes the importance of raising local wisdom as an integral part of education. The integration of local cultural values into the curriculum can enrich education with a more meaningful contextual dimension for students in Indonesia. Overall, the concept of Islamic education in Adabul 'Alim wal Muta'allim not only provides a strong philosophical foundation, but also offers practical direction in shaping an education system that produces intelligent, noble individuals, easy to socialize and ready to compete at the global level.